Optimizing Collaboration Skills in the 21st Century: Recent Innovations in Project Model Differentiated Learning - Anggit Pangestu; Fery Muhamad Firdaus (Universitas Pendidikan Ganesha, 2024)
Collaboration skills are important. Therefore, group learning needs to be held for hands-on experience that results in understanding and effective learning methods. This study aims to analyze the effect of project model differentiated learning on students' collaboration skills in grade V elementary school in science subjects. This type of research is a quasi-experiment with a one-group pretest-posttest design. The sampling technique used was the saturated sampling technique with 26 students. The research instruments used in the form of learning style questionnaires, observation sheets of the learning process in the classroom, and observation sheets to measure student collaboration skills consist of initial and final observation sheets. Data analysis used in this research is descriptive analysis technique and inferential analysis technique with Paired Sample t Test. Before the hypothesis test, the prerequisite test includes the normality test and homogeneity test. The average collaboration skills of grade V students before being given treatment using the differentiated learning project model were none in the Very High category, 9.99% in the High category, 70.76% in the Medium category, and 19.76% in the Low category. After being given treatment using a differentiated learning project model, there were 9.23% in the Very High category, 59.23% in the High category, 31.54% in the Moderate category, and none in the Low category. Furthermore, data processing is carried out with t-value ≥ critical t-value (39.034 > 2.05954), which indicates that there is a positive effect of the differentiated learning project model on student collaboration skills in grade V elementary school.